2017
DOI: 10.3390/ijms19010007
|View full text |Cite
|
Sign up to set email alerts
|

Is Osteopontin a Friend or Foe of Cell Apoptosis in Inflammatory Gastrointestinal and Liver Diseases?

Abstract: Osteopontin (OPN) is involved in a variety of biological processes, including bone remodeling, innate immunity, acute and chronic inflammation, and cancer. The expression of OPN occurs in various tissues and cells, including intestinal epithelial cells and immune cells such as macrophages, dendritic cells, and T lymphocytes. OPN plays an important role in the efficient development of T helper 1 immune responses and cell survival by inhibiting apoptosis. The association of OPN with apoptosis has been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 127 publications
(132 reference statements)
2
21
0
Order By: Relevance
“…Different isoforms, terminal fragments and posttranscriptional modifications of OPN may yield different impact as described in acute brain injury (384,385,386). Finally, OPN binds to multiple integrins and other receptors on multiple cell types, possibly mediating distinct phenotypic changes (387).…”
Section: Osteopontinmentioning
confidence: 99%
“…Different isoforms, terminal fragments and posttranscriptional modifications of OPN may yield different impact as described in acute brain injury (384,385,386). Finally, OPN binds to multiple integrins and other receptors on multiple cell types, possibly mediating distinct phenotypic changes (387).…”
Section: Osteopontinmentioning
confidence: 99%
“…Notably, the SPP1 gene encodes osteopontin (OPN) whose secreted isoform has been found to be chemotactic to immune cells [ 17 ] and may represent a conserved pro-fibrogenic response to chronic liver injury [ 18 ]. OPN has been implicated in various chronic liver diseases including chronic hepatitis and alcoholic liver disease [ 19 ]. OPN upregulation during liver injury and fibrosis represents a conserved repair-response, and thus OPN levels may provide a useful biomarker for liver fibrosis in NASH in addition to other chronic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a recent study from Duke University demonstrated that advanced fibrosis (stage 3–4 vs fibrosis stage 0–1) in NAFLD was associated with upregulation of OPN [ 20 ]. In addition to a pro-fibrogenic role for OPN, it also has several pro-inflammatory properties targeting several innate immune cell populations including macrophages, neutrophils and natural killer cells [ 19 ]. A recent study in a murine NASH model demonstrated that antibodies targeting OPN not only attenuated fibrosis but also inflammation, suggesting that targeting OPN in the early stages of NAFLD may be effective in preventing the progression to NASH and fibrosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Successful replication of a virus relies on the ability to block or delay apoptosis until sufficient progeny have been produced [69]. OPN has been reported to provide the antiapoptotic signal through binding to α v β 3 [70] and CD44 variants v6 and/or v7 [15,[71][72][73]. Thus, it is possible that OPN signaling may help to bypass apoptosis and thereby favor the spread of WNV infection in the CNS.…”
Section: Opn and Wnvmentioning
confidence: 99%